Synthesis of molecularly imprinted polymer for removal of Congo red - Showkat, Ahmad Bhawani; Syed Rizwan, Shafqat; Salma, Bakhtiar; Mohamad Nasir, Mohamad Ibrahim (Cham, Switzerland : Springer Nature, 2020)
Congo red (CR) is an anionic azo dye widely used in many industries including pharmaceutical, textile, food and paint industries. The disposal of huge amount of CR into the various streams of water has posed a great threat to both human and aquatic life. Therefore, it has become an important aspect of industries to remove CR from diferent water sources. Molecular imprinting technology is a very slective method to remove various target pollutant from environment. In this study a precipitation polymerization was employed for the efective and selective removal of CR from contaminated aqueous media. A series of congo red molecularly imprinted polymers (CR-MIPs) of uniform size and shape was developed by changing the mole ratio of the components. The optimum ratio (0.1:4: 20, template, functional monomer and cross-linking monomer respectively) for CR1-MIP from synthesized polymers was able to rebind about 99.63% of CR at the optimum conditions of adsorption parameters (contact time 210 min, polymer dosage 0.5 g, concentration 20 ppm and pH 7). The synthesized polymers were characterized by various techniques such as Fourier Infra-red spectroscopy (FTIR), scanning electron microscopy (SEM), Thermogravimetric analysis (TGA), energydispersive X-ray spectroscopy (EDX), and Brumauer–Emmett–Teller (BET). The p